Optical and morphological properties of tetragonal Cu₂ZnSnS₄ thin films grown from sulphide precursors at lower temperatures - Babichuk, I.S.; Yukhymchuk, V.O.; Semenenko, M.O.; Klyui, N.I.; Caballero, R.; Hreshchuk, O.M.; Lemishko, L.S.; Babichuk, L.V.; Ganus, V.O.; Leon, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Optical constants of Cu₂ZnSnS₄ thin films formed using thermal annealing of pre-deposited layers of copper, zinc and tin sulphides on glass substrates at different temperatures and ambient atmosphere were determined. It has been shown that films grown at lower temperatures have the tetragonal structure of kesterite, and the corresponding value of the optical band gap is 1.47 eV.